2015
DOI: 10.1186/s12936-014-0532-z
|View full text |Cite
|
Sign up to set email alerts
|

Malaria incidence and assessment of entomological indices among resettled communities in Ethiopia: a longitudinal study

Abstract: BackgroundPopulation resettlement has been considered among factors that may increase risk of malaria transmission. This study reports, the impact of resettlement on malaria incidence and entomological indices among communities resettled in suburbs of Jimma town, southwestern Ethiopia.MethodsA cohort of 604 study participants (302 resettlers and 302 non-resettlers) was monthly followed-up from September to November 2013 using active case detection. Moreover, longitudinal entomological study was conducted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 28 publications
4
52
5
Order By: Relevance
“…This might be due to the higher risk of exposure to infectious mosquito bites in the resettlement villages. 12 The presence of vector-breeding sites such as pits dug for plastering and brickmaking made by new settlers during house construction could be prolific mosquito breeding habitats, which in turn may result in higher mosquito abundance in the resettlement villages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to the higher risk of exposure to infectious mosquito bites in the resettlement villages. 12 The presence of vector-breeding sites such as pits dug for plastering and brickmaking made by new settlers during house construction could be prolific mosquito breeding habitats, which in turn may result in higher mosquito abundance in the resettlement villages.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size determination and sampling techniques are described elsewhere. 12 Baseline sociodemographic and socioeconomic characteristics of each household were collected using a semistructured questionnaire. A unique identification card was given to each household member at baseline.…”
Section: -15mentioning
confidence: 99%
“…Plasmodium infections, albeit in a low number of samples, have been recorded in An. coustani in south-western Ethiopia [112], although neither infections nor mosquito identities were confirmed molecularly, and more recently in southern and eastern Zambia [56,116]. In the latter study three molecularly distinct species of An.…”
Section: Cryptic Species and Novel Vectorsmentioning
confidence: 99%
“…An. pharoensis is commonly found in Sudanese and Sahelian regions, but has been implicated in malaria transmission in many parts of Africa such as Nigeria, Guinea-Bissau, Mauritania, Senegal, Egypt, Ethiopia, Chad, Kenya, Tanzania, and possibly Zambia [56,100,102,103,104,105,106,107,108,109,110,111,112]. This species also demonstrates exophilic and/or exophagic behaviors such that they might elude indoor vector control.…”
Section: Cryptic Species and Novel Vectorsmentioning
confidence: 99%
“…However, it has been observed that after primary vectors are reduced in a population, alternative vectors have the potential to sustain malaria transmission (Antonio-Nkondjio et al 2006). Previous studies have indicated the presence of P. falciparum parasites in these alternative vectors in Kenya, Ethiopia, Zambia, and other regions in Africa (Stevenson et al 2012, Degefa et al 2015, Lobo et al 2015, Nepomichene et al 2015a, St. Laurent et al 2016, Stevenson et al 2016a).…”
Section: Introductionmentioning
confidence: 99%